Analysis Analysis of Mobile-Based Archive Management Information System Design - Watanabe, Osamu; Delmo, Critson; Ridho, Taufik (Journal of Information Systems and Technology Research, 2023)
Information technology has become a very common thing in today's society, therefore with the existence of fast and easy information technology it is expected to be able to process the desired information. At this time the existence of information systems presents a new innovation. The rapid development of information technology has penetrated into various sectors including offices. In the digital era, people are increasingly aware that communication technology is an important tool in dealing with the increasingly rapid flow of information. Information has developed and arrived in the digital era, one of which is information processing which has developed from conventional to digitally managed. As a memory center for organizations or agencies, letters are something important and need to be stored properly. But storage is still done conventionally, it will be difficult when you want to do a search. This study aims to design a mail archive information system using qualitative methods as a research method, UML as a system design that will facilitate the flow of research in designing systems and using a waterfall as a system development method. The results of this study are in the form of a design for a mail archive information system which is expected to be able to solve this problem.